Logo Effects on Brand Extension Evaluations from the Electrophysiological Perspective - Shang, Qian; Pei, Guanxiong; Dai, Shenyi; Wang, Xiaoyi (Frontiers in Neuroscience, 2017)
Brand extension typically has two strategies: brand name extension (BN) and brand logo extension (BL). The current study explored which strategy (BN or BL) better enhanced the success of dissimilar brand extension and product promotion in enterprises. Event-related potentials (ERPs) were used to investigate electrophysiological processes when subjects evaluated their acceptance of the brand extension using a combined picture of S1 and S2. S1 was a famous brand presented by two identity signs (brand name and brand logo). S2 was a picture of an extension product that belonged to a dissimilar product category than S1. The behavior data showed that BL was more acceptable than BN in the dissimilar brand extension. The neurophysiology process was reflected by a less negative N2 component and a larger P300 component in the BL than in the BN. We suggested that N2 reflected a whole conflict between the brand-product combination and the long-term memory and that P300 could be regarded as the reflection of the categorization process in the working memory.